Burden and impact of congenital syndromes and comorbidities among adults with congenital heart disease. (1st August 2017) - Bracher, Isabelle; Padrutt, Maria; Bonassin, Francesca; Santos Lopes, Bruno; Gruner, Christiane; Stämpfli, Simon F.; Oxenius, Angela; De Pasquale, Gabriella; Seeliger, Theresa; Lüscher, Thomas F.; Attenhofer Jost, Christine; Greutmann, Matthias
Abstract: Background: Our aim was to assess the overall burden of congenital syndromes and non-cardiac comorbidities among adults with congenital heart disease and to assess their impact on circumstances of living and outcomes. Methods: Within a cohort of 1725 adults with congenital heart defects (65% defects of moderate or great complexity) followed at a single tertiary care center, congenital syndromes and comorbidities were identified by chart review. Their association with arrhythmias, circumstances of living and survival was analyzed. Results: Within the study cohort, 232 patients (13%) had a genetic syndrome, 51% at least one comorbidity and 23% ≥ 2 comorbidities. Most prevalent comorbidities were systemic arterial hypertension (11%), thyroid dysfunction (9%), psychiatric disorders (9%), neurologic disorders (7%), chronic lung disease (7%), and previous stroke (6%). In contrast to higher congenital heart defect complexity, the presence of comorbidities had no impact on living circumstances but patients with comorbidities were less likely to work full-time. Atrial arrhythmias were more common among patients with moderate/great disease complexity and those with comorbidities but were less common among patients with congenital syndromes ( p < 0.01 for all comparisons). Patients with ≥ 2 comorbidities had lower survival estimates compared to those with ≤ 1 comorbidity ( p = 0.013). Conclusion: Congenital syndromes and comorbidities are highly prevalent in adults with congenital heart disease followed at specialist centers and add to the overall complexity of care. The presence of these additional factors has an impact on living circumstances, is associated with arrhythmias and needs to be further explored as prognostic markers.